Design of a gate driver for SiC MOSFET module for applications up to 1200 V. Issue 7 (1st May 2020) - Batard, Christophe; Ginot, Nicolas; Bouguet, Christophe
Abstract : Nowadays new silicon carbide (SiC) metal‐oxide‐semiconductor field‐effect transistors (MOSFETs) are available in the market and they are expected to replace, in the next few years, the insulated gate bipolar transistor (IGBT) and Si‐MOSFET in power electronic converters. SiC MOSFET transistors must be controlled by a dedicated circuit called 'gate driver' which ensures the switching orders transmission, the users' safety and the switching cell integrity. The design of a gate driver dedicated to a SiC MOSFET module for applications up to 1200 V is described in this study. Galvanic isolation of control signals and power supplies, the power supply structure, SiC MOSFET switching orders and protection functions are detailed. Essential functions such as the short circuit detection and the implementation of the soft shut down are expanded. The developed gate driver is tested and validated. Experimental measurements allow for the validation of the good functioning of the developed gate driver in a highly disturbed environment.